What is Old is New Again: A Systemic Approach to the Challenges of Calculus Instruction. Issue 6 (3rd July 2018) - Carreon, Fernando; DeBacker, Stephen; Kessenich, Paul; Kubena, Angela; LaRose, P. Gavin
Abstract: In the abstract for Calculus for a New Century: A Pump, Not a Filter, Lynn Steen wrote: "The authors agree on the forces that are reshaping calculus, but disagree on how to respond to these forces. They agree that the current course is not satisfactory, yet disagree about new content emphases. They agree that the neglect of teaching must be repaired, but do not agree on the most promising avenues for improvement." Over a quarter century later, Steen's description of the calculus landscape applies equally well, though some of the forces shaping it have changed. Students still arrive at their colleges and universities with marginal backgrounds in mathematics, but today those backgrounds frequently include a course called calculus. And while in 1988 technology was widely viewed as a tool for enhancing student understanding, today it is often used by students as a crutch to get answers while avoiding, or just failing to comprehend their lack of, understanding. In this paper we describe a systemic, institutional approach to addressing the challenges facing calculus instruction today, an approach which is rooted in the University of Michigan's experience over the last 25 years, starting with the implementation of "reformed calculus" in the early-1990s. We reflect on the ways in which Michigan's approach is successful in managing emerging challenges, and consider some areas in which further work is still needed.